Hypurpurins A-P, furanolabdane diterpenoids from the aerial parts of Hypoestes purpurea and their bioactivities - Lin-Fen Ding; Bin Cheng; Mei-Yi Zhang; Shi-Huan Yin; Xin-Ying Wang; Lu Sai; Hui-ling Zhou; Xuan Jiang; Jia Su; Xing-De Wu (Phytochemistry, 2026)

Steering catalytic pathways via nanoconfinement-tuned d-band centers in Fe clusters - Hong-Lin Zhang; An-Qi Kang; Hai-Yin Xu; Wei-Ping Xiong; Hai-Hao Peng; Yuan-Ling Luo; Mei-Ying Jia; Zhao-Hui Yang (Chemical Engineering Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Correction to: Isolation of Proteus sp. Closely Related to P. Vulgaris (Vulgaris/hauseri Complex) from Ornamental Koi (Cyprinus rubrofuscus) and its Pathogenicity - Crystal Jia Jing Lim; Hung Hui Chung; Melinda Mei Lin Lau; Cindy Jia Yung Kho; Leonard Whye Kit Lim; Kristene Ling Yong; Pei Xuan Hew (Current Microbiology, 2026)

Multi-strain Bacillus Probiotics has Advantages in Improving Abnormal Behavior and Intestinal Flora in Rats of Autism Spectrum Disorder - Qi-qi Bai; Ji Chen; Lu-lu Dong; Mei-lin Jin; Bo-kai Hu; Yu Gan; Chen-ye You; Jing Hui (Current Microbiology, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Monitoring photochemical reactions catalyzed by nano-titanium dioxide using electrospray laser desorption ionization mass spectrometry - Min-Zong Huang; Hsin-Hui Liang; Chi-Yang Lee; Shu-Yao Lin; Chun-Mei Wu; Jentaie Shiea (Analytica Chimica Acta, 2026)

Casein-liposome complex loading basil essential oil: Preparation, antibacterial effect, and preservative effect on braised beef - Yunshuang Man; Hui Tang; Yudi Wang; Rongrong Yang; Dongling Yan; Qianqian Yu; Lang Zhang; Lin Mei; Jun Qi; Lele Shao (Food Chemistry, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Tripterygium wilfordii Hook. f.: A comprehensive review on phytochemical, pharmacological and tissue-specific distribution of active components - Chang-Sheng Gao; Pei-Lin Su; Mei-Ya Lian; Zhi-Kang Duan; Shu-Hui Dong; Shao-Jiang Song (Phytochemistry, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Adjuvant-metal-ion-chelating PTEN mRNA with cell-membrane-coating augments the immune sensitivity for precise cancer immunotherapy - Mengyu Guo; Jin-Cheng Guo; Haodong Yao; Fene Gao; Lina Zhao; Lu Cai; Xuan Fan; Lin Bao; Xin Li; Xiaoyu Zhang; Mingdi Hu; Jie Mei; et al. (Science Bulletin, 2026)

Biodegradation of three xanthates with different carbon chains in flotation wastewater - Yuhang Cai; Jing-Yuan Zhai; Guo-Hui Zhang; Mei-Qi Lin; Yi-Hao Luo (Journal of Hazardous Materials, 2026)

Thermo-mechanical pre-treatments modulate the structure, protein and starch digestibility, and thermal and pasting properties of sorghum flour - Sumi Shah; Umar Shah; Adil Gani; Amy Hui-Mei Lin; Darren Greetham; Rewati R. Bhattarai (Food Chemistry, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Correction to: Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2026)

Isolation of Proteus sp. Closely Related to P. Vulgaris (Vulgaris/hauseri Complex) from Ornamental Koi (Cyprinus rubrofuscus) and its Pathogenicity - Crystal Jia Jing Lim; Hung Hui Chung; Melinda Mei Lin Lau; Cindy Jia Yung Kho; Leonard Whye Kit Lim; Kristene Ling Yong; Pei Xuan Hew (Current Microbiology, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Clastic record from Northern Tethyan Himalaya: Implication for the initial India-Asian collision in the western Yarlung-Zangpo suture zone, South Tibet - Xu-dong Guo; Lin Ding; Fu-long Cai; Gui-zhen Guo; Xiao-yan Xu; Peng Han; Chang-jun Gu; Mei-yu Liu; Xiang-li Ding; Xu Liu; Xin-lei Li; Deng Zeng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Machine learning intelligently selects feature values to construct a sensor array based on tri-functional Mn-doped covalent organic polymer nanozymes for identifying flavonoid compounds - Guo-Qi Zhang; Wen-Cai Jiang; Xiao-Mei Li; Ren-Jie Li; Yi Feng; Ri-Ge Li Nai; Hui-Lin Cheng; Zhi-Bo Hou; Xiao-Jun Luo; Yan Zhao (Food Chemistry, 2025)

Inverse Admittance Characteristics of Gastric Cancer Cells Measured by a Validated Dielectrophoretic Microfluidic Platform - Jia‑Jiun Tsai; Yun-Jung Tsai; Mei Yu Huang; Chun-Ping Jen; Shu-Hui Lin (Journal of Medical and Biological Engineering, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Protective effects of microalgal macular pigment on diabetic retinopathy upon blue light irradiation induced oxidative stress, inflammation, and MAPK pathways - Meng-Wei Lin; Cheng-Han Lin; Wei-Hong Chiu; Hui-Fang Chang; Wai-Man Cheang; Chien-Chun Chang; Vivian C.H. Wu; Chih-Sheng Lin; Chiu-Mei Kuo (Food Research International, 2025)

Complex of butyric acid with the amorphous region of starch granules via high-pressure processing - Amy Hui-Mei Lin; Shaun Yong Jie Sim; Choy Eng Nge; Ting-Jang Lu; Nur Syahirah Amirruddin; Amanda Xin Yi Sng; Kai Ting Wong; Yoganathan Kanagasundaram; Andrea Gómez-Maqueo; Hui Yu Sim (Food Chemistry, 2025)

Functional oligosaccharides derived from the degradation of natural Dendrobium polysaccharides by human gut microbes regulate physiological factors associated with type-2 diabetes - Ming-Che Cheng; Hsi-Mei Chen; Bao-Jiun Bai; Tsu-Yuan Chang; Meng-Chin Chen; Yen- Ting Lin; Chi-Kung Ni; Mei-Kuang Lu; Hui-Kang Liu; Chia-Chuan Chang (Phytochemistry Letters, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

The Antimicrobial Peptide Tilapia Piscidin 4 Induced the Apoptosis of Bladder Cancer Through ERK/SIRT1/PGC-1α Signaling Pathway - Chun-Feng Chang; Po-Chih Chang; Yi-Chen Lee; Chieh-Yu Pan; Hui-Min Chang; Wan-Ju Wu; Mei-Ying Lin; Chung-Yi Chen; Zhi-Hong Wen; Chien-Hsing Lee (Probiotics and Antimicrobial Proteins, 2025)

Development of single nucleotide polymorphisms markers associated with disease resistance towards Pseudomonas koreensis in empurau (Tor tambroides) using T-Plex ARMS PCR assay - Melinda Mei Lin Lau; Hung Hui Chung; Cindy Jia Yung Kho; Han Ming Gan; Azham Zulkharnain (Aquaculture International, 2025)

Mineralogical insights into the release behaviors of potentially toxic elements from the indigenous Zn smelting slags dumping sites - Ze-Lin Xu; Mei-Chun Zhou; Jin-Hui Miao; Wen-Chu Zhao; Rong-Bing Fu; Da-Mao Xu (Process Safety and Environmental Protection, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Advances in research on the control of pollen tube growth by calcium in higher plants - Yi Hua Lin; Mei Zhen Lin; Hui Qiao Tian; Dong Xiao Li (Plant Science, 2025)

Rapid evaluation of apigenin bioavailability and hypouricemic bioactivity by targeted metabolomics study in enterohepatic microenvironment mimetic cell culture model - Su-Jung Hsu; Hui-Chen Chung; Chia-Hsuan Chang; Yi-Chi Liao; Ta-Wei Liu; Shu-Mei Lin; Ching-Kuo Lee (Food Research International, 2025)

Beneficial impact of MTGase-modified fish gelatin on collagen supplementation in rats: Insights from serum metabolomics and gut microbiota - Chun-Yan Peng; Ting Fang; Hao-Bin Lin; Ni Zhang; Zi-Zi Hu; Hai-tao Wang; Ming-Hui Su; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2025)

In search of nanofiltration membranes for efficient lithium extraction from carbonate-type salt lakes - Ren-Jie Fan; Chun-Xu Zhang; Fujun Xiong; Lin-Hui Niu; Xiang-Xuan Ruan; Xiaohu Wang; Zhen-Yuan Wang; Mei-Ling Liu; Shi-Peng Sun; Weihong Xing (Desalination, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Bioactivity-guided isolation of potent inflammasome and mitochondria damage inhibitory diterpenoids from Orthosiphon wulfenioides - Wen-Chao Tu; Peng-Yun Yang; Xing-Jie Zhang; Yuan-Lin Kong; Bo Li; Hui-Juan Wang; Muhammad Aurang Zeb; Xiao-Li Li; Mei-Feng Liu; Wei-Lie Xiao (Phytochemistry, 2025)

High performance piperidinium based anion exchange membranes with different twisted backbone structures for fuel cells - Ying Jie Liu; Guo Liang Zhang; Yong Qi Hu; Hui Peng; Li Wei Lai; Ai Mei Zhu; Qiu Gen Zhang; Qing Lin Liu (Chemical Engineering Journal, 2025)

Inactivation and sublethal injury of Salmonella Typhimurium on beef and in aqueous solution treated with lactic acid - Yunshuang Man; Mengjiao Zhang; Hui Tang; Rui Wen; Rongrong Yang; Lin Mei; Jun Qi; Ruitong Dai; Guoyuan Xiong; Lele Shao (Food Research International, 2025)

Therapeutic drug monitoring of methotrexate by disposable SPCE biosensor for personalized medicine - Hui Liu; Yi-Wei Liu; Ruo-Yu Yang; Mei-Juan Wu; Zi-Wei Yu; Jing-Wen Han; Chen-Zhi Zhang; Pin-Fang Huang; Ai-Lin Liu; Meng-Meng Liu (Analytica Chimica Acta, 2025)

Performance of Convolutional Neural Network Models in Meningioma Segmentation in Magnetic Resonance Imaging: A Systematic Review and Meta-Analysis - Ting-Wei Wang; Jia-Sheng Hong; Wei-Kai Lee; Yi-Hui Lin; Huai-Che Yang; Cheng-Chia Lee; Hung-Chieh Chen; Hsiu-Mei Wu; Weir Chiang You; Yu-Te Wu (Neuroinformatics, 2024)
Background Meningioma, the most common primary brain tumor, presents significant challenges in MRI-based diagnosis and treatment planning due to its diverse manifestations. Convolutional Neural Networks (CNNs) have shown promise in improving the accuracy and efficiency of meningioma segmentation from MRI scans. This systematic review and meta-analysis assess the effectiveness of CNN models in segmenting meningioma using MRI. Methods Following the PRISMA guidelines, we searched PubMed, Embase, and Web of Science from their inception to December 20, 2023, to identify studies that used CNN models for meningioma segmentation in MRI. Methodological quality of the included studies was assessed using the CLAIM and QUADAS-2 tools. The primary variable was segmentation accuracy, which was evaluated using the Sørensen–Dice coefficient. Meta-analysis, subgroup analysis, and meta-regression were performed to investigate the effects of MRI sequence, CNN architecture, and training dataset size on model performance. Results Nine studies, comprising 4,828 patients, were included in the analysis. The pooled Dice score across all studies was 89% (95% CI: 87–90%). Internal validation studies yielded a pooled Dice score of 88% (95% CI: 85–91%), while external validation studies reported a pooled Dice score of 89% (95% CI: 88–90%). Models trained on multiple MRI sequences consistently outperformed those trained on single sequences. Meta-regression indicated that training dataset size did not significantly influence segmentation accuracy. Conclusion CNN models are highly effective for meningioma segmentation in MRI, particularly during the use of diverse datasets from multiple MRI sequences. This finding highlights the importance of data quality and imaging sequence selection in the development of CNN models. Standardization of MRI data acquisition and preprocessing may improve the performance of CNN models, thereby facilitating their clinical adoption for the optimal diagnosis and treatment of meningioma.

Nitrogen fixation of different seasons and parts of seagrass Enhalus acoroides in Xincun Bay, northern South China Sea - Zhen-Zhen Wu; Xiao-Mei Li; Hui Zhao; Long Wei; Jun-De Dong; Mei-Lin Wu (Regional Studies in Marine Science, 2024)

Molecular properties, structure, neurotrophic and anti-inflammatory activities of cultured secondary metabolites from the cultures of the mushroom Cyathus striatus CBPFE A06 - Jing Wei; Mei-Yu Ye; Zhen-Xin Wang; Yi-Lin Zhang; Xuan-Sheng Hu; He-ping Hui; Yi-tong Liu; Jianzhao Qi (Natural Product Research, 2024)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Insufficient FUNDC1-dependent mitophagy due to early environmental cadmium exposure triggers mitochondrial redox imbalance to aggravate diet-induced lipotoxicity - Cai-Yu Lian; Hui-Jia Li; Wei-Hao Xia; Yue Li; Xue-Lei Zhou; Du-Bao Yang; Xue-Mei Wan; Lin Wang (Environmental Pollution, 2024)

Agricultural management reshaped the diversity patterns and community assembly of rhizosphere bacterial communities in a desert farming system - Wen-Hui Lian; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Zhi-Liang Lin; Chao-Jian Hu; Jia-Rui Han; Wen-Jun Li; Lei Dong (Applied Soil Ecology, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Analysis of two-dimensional consolidation behavior of soils under cyclic loading considering exacerbated tunnel leakage - Sen-Lin Xie; An-Feng Hu; Zhi-Rong Xiao; Mei-Hui Wang; Xun-Jian Hu; Gabriele Della Vecchia; Stefano Mariani (Computers and Geotechnics, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Molecular Cloning and Functional Analysis of ScHAK10 Gene Promoter from Sugarcane (Saccharum officinarum L.) - Hai-Bin Luo; Cheng-Mei Huang; Hui-Qing Cao; Yuan-Wen Wei; Lin Xu; Kai-Chao Wu; Zhi-Nian Deng; Xing-Jian Wu; Li-Ping Ye; Xiao-Ping Yi (Tropical Plant Biology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Colletotrichum cliviicola as a new causal agent causing leaf spot disease on Tilia tomentosa moench (silver linden) in China - Lin Chang; Xue-hai Li; Yi-lin Li; Zi-wen Gao; Yue-mei Zhang; Ning-Li; Zhao-lei Qu; Yi-hong Yang; Hui Sun (Crop Protection, 2024)

Selection of vaccine candidates against Pseudomonas koreensis using reverse vaccinology and a preliminary efficacy trial in Empurau (Tor tambroides) - Cindy Jia yung Kho; Melinda Mei Lin Lau; Hung Hui Chung; Koji Fukui (Fish & Shellfish Immunology, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

Isolation, identification and characterisation of Pseudomonas koreensis CM-01 isolated from diseased Malaysian mahseer (Tor tambroides) - Melinda Mei Lin Lau; Cindy Jia Yung Kho; Hung Hui Chung; Azham Zulkharnain (Fish & Shellfish Immunology, 2024)

Two unprecedented neuroprotective 2-(2-phenylethyl)chromone derivatives from cultivated “Qi-Nan” agarwood of Aquilaria sinensis - Lin Zhang; Hao Wang; Wen-Hua Dong; Jun Zeng; Li Yang; Wei Li; Hui-Qin Chen; Jing-Zhe Yuan; Cai-Hong Cai; Zhen-Yu Li; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2024)

Combined analysis of transcriptomics and metabolomics provide insights into the antibacterial mechanism of bacteriocin XJS01 against multidrug-resistant Staphylococcus aureus - Jian-Ping Ying; Chao-Min Fu; Yan-Chun Wu; Ya-Mei Chen; Xiao-Yu Liu; Qi-Lin Zhang; Hui Liu; Ming-Zhong Liang (Science of The Total Environment, 2024)

Migration of phosphorus in pig manure during pyrolysis process and slow-release mechanism of biochar in hydroponic application - Ru-Qing Jiang; Guang-Wei Yu; Lin-Hui Yu; Yu Wang; Chang-Jiang Li; Zhen-Jiao Xing; Xi-Mei Xue; Yin Wang; Cheng Yu (Science of The Total Environment, 2024)

Timing of India-Asia suturing: Evidence from a remnant peripheral foreland basin in Xigaze, South Tibet - Xu-Dong Guo; Lin Ding; Qiu-yun Guan; Deng Zeng; Chao Wang; Gui-zhen Guo; Hou-Qi Wang; Mei-Yu Liu; Xiang-Li Ding; Muhammad Qasim; Ya-Hui Yue; Jing Xie; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Scalable, bio-inspired and self-floating bi-layer polyurethane foam solar evaporator with excellent capillary hydrodynamic effect - Jing Lin; Mei Wu; Hao Fang; Mengyue Wu; Shikuo Li; Hui Zhang; Yu Jiang; Fangzhi Huang (Chemical Engineering Journal, 2024)

Unraveling fluorescent mechanism of biomass-sourced carbon dots based on three major components: Cellulose, lignin, and protein - Tian-xiang Li; De-fang Zhao; Lin Li; Yang Meng; Yu-hui Xie; Dong Feng; Feng Wu; Delong Xie; Yuxin Liu; Yi Mei (Bioresource Technology, 2024)

Oncogenic and immunological roles of RACGAP1 in pan-cancer and its potential value in nasopharyngeal carcinoma - Cheng-shan Zheng; Wei-mei Huang; Hong-mei Xia; Jing-lin Mi; Yuan-qing Li; Hui-qing Liang; Li Zhou; Zhou-xue Lu; Fang Wu (Apoptosis, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Incorporation of microalgae (Nannochloropsis oceanica) into plant-based fishcake analogue: Physical property characterisation and in vitro digestion analysis - Lin Zhao; Hui Mei Khang; Juan Du (Food Hydrocolloids, 2024)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Expression of a periplasmic β-carbonic anhydrase (CA) gene is positively correlated with HCO3- utilization by the gametophytes of Saccharina japonica (Phaeophyceae, Ochrophyta) - Hui-Min Hao; Yan-Hui Bi; Ning-Ning Wei; Pei-Chong Lin; Shou-Hua Mei; Zhi-Gang Zhou (Journal of Applied Phycology, 2023)

Estimation of soil organic matter by in situ Vis-NIR spectroscopy using an automatically optimized hybrid model of convolutional neural network and long short-term memory network - Xiaoqing Wang; Mei-Wei Zhang; Qian Guo; Hua-Lei Yang; Hui-Li Wang; Xiao-Lin Sun (Computers and Electronics in Agriculture, 2023)

The impact of cooperative innovation network on innovation output of China's marine biomedical industry - Xiu-Mei Fu; Ying-Hui Han; Ying Liu; Qiao-Qiao Qi; Yan-Xin Tan; Meng Gao; Chun-Yu Lin (Ocean & Coastal Management, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Evaluation of the impacts of ozone on the vegetation productivity of woodland and grassland ecosystems in China - WANG Qinyi; HUANG Mei; WANG Shaoqiang; CHEN Bin; LIU Zhenhai; WANG Zhaosheng; CHEN Shiliang; LI Hui; ZHU Tongtong; LI Donghui; LI Yuelin; Lin Hu; et al. (Ecological Modelling, 2023)

Effects of dietary starch and metformin levels on the growth performance, body composition, hepatic glycolipid metabolism, and liver histology of juvenile largemouth bass Micropterus salmoides - Qin-Qin Liu; Ru Xia; Xin Deng; Hui-Jun Yang; Li Luo; Shi-Mei Lin; Chuan-Jie Qin; Yong-Jun Chen (Aquaculture, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Generating slow digestibility in cooked potatoes by modulating starch accessibility to α-amylase and mucosal α-glucosidase to different levels - Andrea Gómez-Maqueo; Alvaro Ferreira-Lazarte; Nur Syahirah Amirruddin; Amy Hui-Mei Lin (Food Hydrocolloids, 2023)

Whole-Genome Sequencing of Pseudomonas koreensis Isolated from Diseased Tor tambroides - Cindy Jia Yung Kho; Melinda Mei Lin Lau; Hung Hui Chung; Ivy Yee Yen Chew; Han Ming Gan (Current Microbiology, 2023)

Special issue: Health, it matters: responsible mission for landscape and ecological engineering - Chun-Yen Chang; Hui-Mei Chen; Bau-Show Lin (Landscape and Ecological Engineering, 2023)

Callose wall and sporoderm characteristics during the anther development stage of Dendrobium officinale - Wei Deng; Mei Zhen Lin; Hui Qiao Tian (Flora, 2023)

Artificial intelligence and visual analytics in geographical space and cyberspace: Research opportunities and challenges - Min Chen; Christophe Claramunt; Arzu Çöltekin; Xintao Liu; Peng Peng; Anthony C. Robinson; Dajiang Wang; Josef Strobl; John P. Wilson; Michael Batty; Mei-Po Kwan; Maryam Lotfian; et al. (Earth-Science Reviews, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Activated AMPK-mediated glucose uptake and mitochondrial dysfunction is critically involved in the glutamate-induced oxidative injury in HT22 cell - Shao-Peng Lin; Jingyi Bu; Shan Ye; Qiangda Xie; Jue-Xian Wei; Xiaofang Yin; Fen Mei; Pei-Yi Lin; Xiao-Hui Chen (Tissue and Cell, 2023)

Prevalence and Subtype Distribution of Blastocystis in Tibetan Sheep in Qinghai Province, Northwestern China - Fan Yang; Jing-min Gou; Bing-ke Yang; Jia-yue Du; Hui-zhong Yao; Mei Ren; Qing Lin (Protist, 2023)

Click-crosslinked in-situ hydrogel improves the therapeutic effect in wound infections through antibacterial, antioxidant and anti-inflammatory activities - Xiong-Xin Lei; Chen-Yu Zou; Juan-Juan Hu; Yan-Lin Jiang; Xiu-Zhen Zhang; Long-Mei Zhao; Tao He; Qing-Yi Zhang; Ya-Xing Li; Jesse Li-Ling; Hui-Qi Xie (Chemical Engineering Journal, 2023)

Osthole increases the radiosensitivity of hepatoma cells by inhibiting GSK-3β/AMPK/mTOR pathway-controlled glycolysis - Hui Huang; Jie Xue; Tao Xie; Mei-Lin Xie (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Plastome evolution and phylogenomics of Impatiens (Balsaminaceae) - He Qiu; Zhi-Hui Zhang; Mei-Zhen Wang; Xin-Jie Jin; Jie-Dong Lin; Hans Peter Comes; Jing-Xuan Chen; Rui-Ning Cui; Ru-Qing Duan; Pan Li (Planta, 2023)

The interaction of MC3R and MC4R with MRAP2a in rainbow trout (Oncorhynchus mykiss) - Hui-Xia Yu; Yang Li; De-Bin Zhong; Xin Ren; Hao-Lin Mo; Ze-Bin Jiang; Jia-Jia Yu; Dong-Mei Xiong; Hai-Xia Liu; Li-Xin Wang (Fish Physiology and Biochemistry, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Biophysical controls on spatial and summer/winter distributions of total and chromophoric dissolved organic matter in the Taiwan Strait - Jia-Jang Hung; Wan-Tzu Lu; Hsin-Mei Yang; Yen-Hui Lin; Laodong Guo (Frontiers in Marine Science, 2022)
This study examined the physical and biogeochemical processes that determine the spatial and summer/winter distributions of dissolved organic matter (DOM) and chromophoric dissolved organic matter (CDOM) in the Taiwan Strait (TS). The hydrological conditions in the TS varied between early summer and winter because of differences in terrestrial input as well as input from the poleward South China Sea Water (SCSW) during the warm summer and the strong, nutrient-rich, equatorward China Coastal Water (CCW) in winter. Concentrations of dissolved organic carbon (DOC) ranged from 60 to 100 μM-C in early summer and from 70 to 144 μM-C in winter. The average stoichiometric ratio of DOC : DON:DOP was high (353:49:1) in the land-source impacted zones and low (168:21:1) in the SCSW-laden areas, both of which are higher than the Redfield ratio. The concentrations of DOC and nutrients were higher in the western TS (on the coast of China) than in the eastern TS (on the coast of Taiwan), and the highest concentrations were mostly found in the Minjiang River plume, reflecting the profound effects of freshwater input in early summer and CCW inflow in winter. The absorption and emission characteristics of the CDOM varied to a large extent with locations because of the mixing of the shelf water with different source waters. Although the absorption coefficient (a CDOM (325)) and fluorescence intensity of the terrestrial humic-like CDOM (Ft: Ex/Em= 260/400-460) were both strongly inversely correlated with salinity, as an optical tracer, Ft may be more effective than a CDOM (325) in examining the mixing among source waters, given that a CDOM (325) may be subject to various photobleaching effects in the TS. Ft was also significantly correlated with the concentrations of terrestrially derived nitrate and nitrite (N+N) and silicate. The results of factor analysis elucidated the complexity of the hydrological and biological processes that affect the distributions of DOM and CDOM in the TS.

The optimal combination of Nile red identification, colony polymerase chain reaction, and gas chromatography detection methods in screening for polyhydroxyalkanoicate-producing bacteria - Hung-Che Chou; Chia-Hsin Chen; Hsiao-Kai Chu; Chun-Mei Huang; Hui-Jun Wang; Wei-Lin Tu; Gia-Luen Guo (Archives of Microbiology, 2022)

Spatial–temporal patterns of summer urban islands and their economic implications in Beijing - Lu Lin; Lina Meng; Yingdan Mei; Wenting Zhang; Hui Liu; Weiling Xiang (Environmental Science and Pollution Research, 2022)

Genetic diversity and population structure of Curcuma alismatifolia Gagnep. accessions revealed by SSR markers - Hui-Wen Yu; Ling-Jun Ke; Yi-Lan Xiao; Si-Jia Chen; Yuan-Yuan Li; Qi-Lin Tian; Yun-He Li; Jin-Shui Lin; Luan-Mei Lu (Genetic Resources and Crop Evolution, 2022)

Investigation on grouting diffusion in inclined fracture with flowing water conditions - Jia-fan Zhang; Xun-xun Chen; Yang Liu; Hui-mei Zhang; Chun-lin Wang; Gang Fang (Arabian Journal of Geosciences, 2022)

The management of bone defect using long non-coding RNA as a potential biomarker for regulating the osteogenic differentiation process - Jia-lin Liu; Yan-shi Liu; Mei-jie Zheng; Hui-yu He (Molecular Biology Reports, 2022)
Tissue engineered bone brings hope to the treatment of bone defects, and the osteogenic differentiation of stem cells is the key link. Inducing osteogenic differentiation of stem cells may be a potential approach to promote bone regeneration. In recent years, lncRNA has been studied in the field increasingly, which is believed can regulate cell cycle, proliferation, metastasis, differentiation and immunity, participating in a variety of physiology and pathology processes. At present, it has been confirmed that certain lncRNAs regulate the osteogenesis of stem cells and take part in mediating signaling pathways including Wnt/β-catenin, MAPK, TGF-β/BMP, and Notch pathways. Here, we provided an overview of lncRNA, reviewed its researches in the osteogenic differentiation of stem cells, emphasized the importance of lncRNA in bone regeneration, and focused on the roles of lncRNA in signaling pathways, in order to make adequate preparations for applying lncRNA to bone tissue Engineering, letting it regulate the osteogenic differentiation of stem cells for bone regeneration.

Changes in the growth performance, antioxidant enzymes and stress resistance caused by dietary administration of synbiotic (fructooligosaccharide and probiotics) in juvenile Chinese Mitten Crab, Eriocheir sinensis - Jin-Juan Wan; Jian-lin Pan; Mei-Fang Shen; Hui Xue; Meng-lin Sun; Mei-Qin Zhang; Xi-He Zhu; Xing-kong Ma (Aquaculture International, 2022)

Feasibility and utility of facemask sampling in the detection of SARS-CoV-2 during an ongoing pandemic - Dorothy Hui Lin Ng; Mei Yi Sim; Hong Hong Huang; Jean Xiang Ying Sim; Jenny Guek Hong Low; Jay Kheng Sit Lim (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A Review on the Emerging Asian Aquaculture Fish, the Malaysian Mahseer (Tor tambroides): Current Status and the Way Forward - Melinda Mei Lin Lau; Leonard Whye Kit Lim; Sairatul Dahlianis Ishak; Ambok Bolong Abol-Munafi; Hung Hui Chung (Proceedings of the Zoological Society, 2021)

Identification and characterization of CONSTANS-like genes from Curcuma alismatifolia - Yuan-Yuan Li; Xiao-Huang Chen; Hui-Wen Yu; Qi-Lin Tian; Luan-Mei Lu (Horticulture, Environment, and Biotechnology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

Identification of Aspergillus tubingensis causing pomegranate fruit rot in China - Mei Jun Guo; Qiu Tong Wang; Yuan Hui Cheng; Cheng Lin Hou (Australasian Plant Pathology, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Correction to: Potato Cultivar Susceptibility to Pythium Leak as Influenced by Harvest and Early Storage Temperatures - Andrew K Hollingshead; Nora L. Olsen; Mike Thornton; Jeff S. Miller; Amy Hui-Mei Lin (American Journal of Potato Research, 2020)

Potato Cultivar Susceptibility to Pythium Leak as Influenced by Harvest and Early Storage Temperatures - Andrew K Hollingshead; Nora L. Olsen; Mike Thornton; Jeff S. Miller; Amy Hui-Mei Lin (American Journal of Potato Research, 2020)

Long interpregnancy interval and adverse perinatal outcomes: A retrospective cohort study - Jing Lin; Han Liu; Dan-Dan Wu; Hong-Tao Hu; Hui-Hui Wang; Cheng-Liang Zhou; Xin-Mei Liu; Xiao-Jun Chen; Jian-Zhong Sheng; He-Feng Huang (Science China Life Sciences, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Twist1 Plays an Anti-apoptotic Role in Mutant Huntingtin Expression Striatal Progenitor Cells - Wei-Ping Jen; Hui-Mei Chen; Yow-Sien Lin; Yijuang Chern; Yi-Ching Lee (Molecular Neurobiology, 2020)

High dietary lipid level alters the growth, hepatic metabolism enzyme, and anti-oxidative capacity in juvenile largemouth bass Micropterus salmoides - Yue-Lang Zhou; Jia-Ling Guo; Ren-Jun Tang; Hui-Jia Ma; Yong-Jun Chen; Shi-Mei Lin (Fish Physiology and Biochemistry, 2020)

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Progressive multifocal leukoencephalopathy in a renal transplant patient - Tsu-Chen Lin; Mei-Yi Wu; Hui-Tzung Luh; Shiou-Fu Lin; Chien-Min Lin; Ying-Chi Tseng; Yung-Ching Liu; Mai-Szu Wu (Journal of NeuroVirology, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Mercury–Organic Matter Interactions in Soils and Sediments: Angel or Devil? - Mei He; Lei Tian; Hans Fredrik Veiteberg Braaten; Qingru Wu; Jie Luo; Li-Mei Cai; Jiang-Hui Meng; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Iron chelation inhibits cancer cell growth and modulates global histone methylation status in colorectal cancer - Lin-Lin Cao; Hangqi Liu; Zhihong Yue; Lianhua Liu; Lin Pei; Junxu Gu; Hui Wang; Mei Jia (BioMetals, 2018)

Activating adenosine A1 receptor accelerates PC12 cell injury via ADORA1/PKC/KATP pathway after intermittent hypoxia exposure - Hong-Fang Mei; Neha Poonit; Yi-Chun Zhang; Chu-Yuan Ye; Hui-Lin Cai; Chen-Yi Yu; Yong-Hai Zhou; Bei-bei Wu; Jun Cai; Xiao-Hong Cai (Molecular and Cellular Biochemistry, 2018)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Identifying crack initiation stress threshold in brittle rocks using axial strain stiffness characteristics - Mei-ben Gao; Tian-bin Li; Lu-bo Meng; Chun-chi Ma; Hui-lin Xing (Journal of Mountain Science, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Community responses to dam removal in a subtropical mountainous stream - Hao-Yen Chang; Ming-Chih Chiu; Yi-Li Chuang; Chyng-Shyan Tzeng; Mei-Hwa Kuo; Chao-Hsien Yeh; Hsiao-Wen Wang; Sheng-Hai Wu; Wen-Hui Kuan; Shang-Te Tsai; Kwang-Tsao Shao; Hsing-Juh Lin (Aquatic Sciences, 2017)

Grape hexokinases are involved in the expression regulation of sucrose synthase- and cell wall invertase-encoding genes by glucose and ABA - Xiu-Qin Wang; Li-Li Zheng; Hao Lin; Fei Yu; Li-Hui Sun; Li-Mei Li (Plant Molecular Biology, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

MicroRNA-27a Promotes Inefficient Lysosomal Clearance in the Hippocampi of Rats Following Chronic Brain Hypoperfusion - Hui Che; Yan Yan; Xiao-Hui Kang; Fei Guo; Mei-Ling Yan; Huai-Lei Liu; Xu Hou; Tong Liu; De-Kang Zong; Lin-Lin Sun; Ya-Nan Bao; Li-Hua Sun; et al. (Molecular Neurobiology, 2017)

Effects of soybean meal processing treatments on growth performance, nutrient digestibility, nitrogen and phosphorus excretion in red swamp crayfish, Procambarus clarkii - Jin-juan Wan; Mei-fang Shen; Jian-qing Tang; Hai Lin; Wei-hui Yan; Jia-jia Li; Lin Zhu (Aquaculture International, 2017)

Species-specific effects of leaf litter on seedling emergence and growth of the invasive Flaveria bidentis and its co-occurring native species: a common garden test - Ke-li Li; Hui-yan Li; Chao-he Huangfu; Dian-lin Yang; Hong-mei Liu; Hui Wang (Plant Ecology, 2016)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Context- and time-dependent neurobiological and behavioral sensitization induced by a single morphine exposure in mice - Wang-Jun Qin; Yan-Ting Wang; Peng-Mei Li; Xiao-Xing Wang; Jun-Xu Li; Hamid R. Noori; Rick E. Bernardi; Jian-Hui Liang; Xiang-Lin Zhang (Psychopharmacology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

The small GTP ase MoYpt 7 is required for membrane fusion in autophagy and pathogenicity of M agnaporthe oryzae - Xiao‐Hong Liu; Si‐Miao Chen; Hui‐Min Gao; Guo‐Ao Ning; Huan‐Bin Shi; Yao Wang; Bo Dong; Yao‐Yao Qi; Dong‐Mei Zhang; Guo‐Dong Lu; Zong‐Hua Wang; Jie Zhou; et al. (Environmental Microbiology, 2015)
Summary R ab GTP ases are required for vesicle–vacuolar fusion during vacuolar biogenesis in fungi. To date, little is known about the biological functions of the R ab small GTP ase components in M agnaporthe oryzae . In this study, we investigated MoYpt 7 of M . oryzae , a homologue of the small R as‐like GTP ase Ypt7 in S accharomyces cerevisiae . Cellular localization assays showed that MoYpt 7 was predominantly localized to vacuolar membranes. Using a targeted gene disruption strategy, a Δ MoYPT7 mutant was generated that exhibited defects in mycelial growth and production of conidia. The conidia of the Δ MoYPT7 mutant were malformed and defective in the formation of appressoria. Consequently, the Δ MoYPT7 mutant failed to cause disease in rice and barley. Furthermore, the Δ MoYPT7 mutant showed impairment in autophagy, breached cell wall integrity, and higher sensitivity to both calcium and heavy metal stress. Transformants constitutively expressing an active MoYPT7 allele ( MoYPT7 ‐ CA , G ln67 L eu) exhibited distinct phenotypes from the Δ MoYPT7 mutant. Expression of MoYPT7 ‐ CA in MoYpt 7 reduced pathogenicity and produced more appressoria‐forming single‐septum conidia. These results indicate that MoYPT7 is required for fungal morphogenesis, vacuole fusion, autophagy, stress resistance and pathogenicity in M . oryzae .

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

The Transcriptome Study of Subtype M2 Acute Myeloblastic Leukemia - A-yang Wu; Hui-cong Yang; Cong-meng Lin; Bi-de Wu; Qi-shui Qu; Yuan-hai Zheng; Hua Wei; Xu-qiao Mei; Zhen-hua Zeng; Xu-dong Ma (Cell Biochemistry and Biophysics, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Inhibition of isoflavone biosynthesis enhanced T-DNA delivery in soybean by improving plant–Agrobacterium tumefaciens interaction - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Xiu-Lin Guo; Hui-Cong Li; Guo-Liang Li; Chun-Zhi Jiang; Meng-Chen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Characteristics of Na+ uptake in sugar beet (Beta vulgaris L.) seedlings under mild salt conditions - Guo-Qiang Wu; Qing-Zhao Shui; Chun-Mei Wang; Jin-Lin Zhang; Hui-Jun Yuan; Shan-Jia Li; Zuo-Jun Liu (Acta Physiologiae Plantarum, 2015)

The wheat NHX antiporter gene TaNHX2 confers salt tolerance in transgenic alfalfa by increasing the retention capacity of intracellular potassium - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Hui-Cong Li; Xiu-Lin Guo; Guo-Liang Li (Plant Molecular Biology, 2015)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Molecular characterisation and expression profiling of the ENO1 gene in the ovarian follicle of the Sichuan white goose - Bo Kang; Dong Mei Jiang; Lin Bai; Hui He; Rong Ma (Molecular Biology Reports, 2014)

MicroRNA Expression Aberration in Chinese Patients with Relapsing Remitting Multiple Sclerosis - Dan Yang; Wei-Zhi Wang; Xue-Mei Zhang; Hui Yue; Bing Li; Lin Lin; Jin Fu (Journal of Molecular Neuroscience, 2014)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Isolation and characterization of lactic acid bacteria from pobuzihi (fermented cummingcordia), a traditional fermented food in Taiwan - Yi-sheng Chen; Hui-chung Wu; Chiung-mei Wang; Chia-chun Lin; Yi-ting Chen; Yu-jyun Jhong; Fujitoshi Yanagida (Folia Microbiologica, 2013)

Winter wheat mapping using temporal signatures of MODIS vegetation index data - Huasheng Sun; Aigong Xu; Hui Lin; Lianpeng Zhang; Yan Mei (International Journal of Remote Sensing, 2012)

Coexisting mutations/polymorphisms of the long QT syndrome genes in patients with repaired Tetralogy of Fallot are associated with the risks of life-threatening events - Shuenn-Nan Chiu; Mei-Hwan Wu; Ming-Jai Su; Jou-Kou Wang; Ming-Tai Lin; Chien-Chih Chang; Hui-Wen Hsu; Ching-Tsuen Shen; Olivier Thériault; Mohamed Chahine (Human Genetics, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Liquefaction potential and post-liquefaction settlement evaluations of the Chuoshui River Alluvial Fan in Taiwan - Muhsiung Chang; Chih-ping Kuo; Ron-eeh Hsu; Shih-hui Shau; Tin-mei Lin (Bulletin of Engineering Geology and the Environment, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Chemical composition of precipitation and its sources in Hangzhou, China - Hong Xu; Xiao-Hui Bi; Yin-Chang Feng; Feng-Mei Lin; Li Jiao; Sheng-Mao Hong; Wen-Gao Liu; Xiao-Yong Zhang (Environmental Monitoring and Assessment, 2011)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

Characterization of a salt-tolerant xylanase from Thermoanaerobacterium saccharolyticum NTOU1 - Kuo-Sheng Hung; Shiu-Mei Liu; Tsuei-Yun Fang; Wen-Shyong Tzou; Fu-Pang Lin; Kuang-Hui Sun; Shye-Jye Tang (Biotechnology Letters, 2011)

Role of microRNA-21 and effect on PTEN in Kazakh’s esophageal squamous cell carcinoma - Wen-jing Ma; Guo-dong Lv; Aerziguli Tuersun; Qing Liu; Hui Liu; Shu-tao Zheng; Cong-gai Huang; Jun-guo Feng; Xing Wang; Ren-yong Lin; Ilyar Sheyhidin; Xiao-mei Lu (Molecular Biology Reports, 2011)

Bacteria associated with an encrusting sponge ( Terpios hoshinota ) and the corals partially covered by the sponge - Sen‐Lin Tang; Mei‐Jhu Hong; Ming‐Hui Liao; Wann‐Neng Jane; Pei‐Wen Chiang; Chung‐Bin Chen; Chaolun A. Chen (Environmental Microbiology, 2011)
Summary Terpios hoshinota , a dark encrusting sponge, is known to be a competitor for space in coral reef environments, and facilitates the death of corals. Although numerous cyanobacteria have been detected in the sponge, little is known of the sponge‐associated bacterial community. This study examined the sponge‐associated bacterial community and the difference between the bacterial communities in the sponge and the coral partially covered by the sponge by analysis of 16S rRNA gene sequences of samples isolated from the sponge covering the corals Favia complanata, Isopora palifera, Millepora sp. , Montipora efflorescens and Porites lutea . The sponge‐associated bacterial community was mainly (61–98%) composed of cyanobacteria, with approximately 15% of these alphaproteobacteria and gammaproteobacteria, although the proportions varied in different sponge samples. The dominant cyanobacteria group was an isolated group closely related to Prochloron sp. The comparison of the bacterial communities isolated from sponge‐free and the sponge‐covered P. lutea showed that covering by the sponge caused changes in the coral‐associated bacterial communities, with the presence of bacteria similar to those detected in black‐band disease, suggesting the sponge might benefit from the presence of bacteria associated with unhealthy coral, particularly in the parts of the coral closest to the margin of the sponge.

Enhancement of salt tolerance in alfalfa transformed with the gene encoding for betaine aldehyde dehydrogenase - Zi-Hui Liu; Hong-Mei Zhang; Guo-Liang Li; Xiu-Lin Guo; Shou-Yi Chen; Gui-Bo Liu; Yan-Min Zhang (Euphytica, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

NYGGF4 homologous gene expression in 3T3-L1 adipocytes: regulation by FFA and adipokines - Ya-ping Zhao; Chun-mei Zhang; Chun Zhu; Xiao-hui Chen; Jia-lin Wang; Chen-bo Ji; Xia Chi; Qin Hong; Yu-zhu Peng; Xi-rong Guo (Molecular Biology Reports, 2010)

Morphological changes of Fusarium oxysporum induced by CF66I, an antifungal compound from Burkholderia cepacia - Xin Li; Hui-Ying Yu; Yi-Feng Lin; Hong-Mei Teng; Lei Du; Guo-Gang Ma (Biotechnology Letters, 2010)

Responses of Mikania micrantha, an Invasive Weed to Elevated CO2: Induction of β-Caryophyllene Synthase, Changes in Emission Capability and Allelopathic Potential of β-Caryophyllene - Rui-Long Wang; Christian Staehelin; Shao-Lin Peng; Wen-Tian Wang; Xi-Mei Xie; Hui-Ning Lu (Journal of Chemical Ecology, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Erratum to: Novel mutations in the connexin43 (GJA1) and GJA1 pseudogene may contribute to nonsyndromic hearing loss - Hui-Mei Hong; Jiann-Jou Yang; Jia-Ching Shieh; Mei-Ling Lin; Shuan-Yow Li (Human Genetics, 2010)

Intratumoral as well as peritumoral lymphatic vessel invasion correlates with lymph node metastasis and unfavourable outcome in colorectal cancer - Mei Lin; Shu-Pei Ma; Hui-Zhong Lin; Ping Ji; Dan Xie; Jian-Xian Yu (Clinical & Experimental Metastasis, 2010)

Effect of PARP-1 deficiency on DNA damage and repair in human bronchial epithelial cells exposed to Benzo(a)pyrene - Gong-hua Tao; Lin-qing Yang; Chun-mei Gong; Hai-yan Huang; Jian-dong Liu; Jian-jun Liu; Jian-hui Yuan; Wen Chen; Zhi-xiong Zhuang (Molecular Biology Reports, 2009)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

A low-pressure gene gun for genetic transformation of maize (Zea mays L.) - Chien-Yuan Kao; Shin-Hui Huang; Chiu-Mei Lin (Plant Biotechnology Reports, 2008)

Juvenile Tilapia (Oreochromis mossambicus) Strive to Maintain Physiological Functions After Waterborne Copper Exposure - Su Mei Wu; Hui Ru Ding; Li-Yih Lin; Yu-Siang Lin (Archives of Environmental Contamination and Toxicology, 2008)

Improved production of pristinamycin coupled with an adsorbent resin in fermentation by Streptomyces pristinaespiralis - Bo Jia; Zhi-Hua Jin; Yin-Lin Lei; Le-He Mei; Ning-Hui Li (Biotechnology Letters, 2006)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

High-level expression of Trigonopsis variabilis D-amino acid oxidase in Escherichia coli using lactose as inducer - Tzann-Shun Hwang; Hui-Mei Fu; Long-Liu Lin; Wen-Hwei Hsu (Biotechnology Letters, 2000)